Modified impact of emotion on temporal discrimination in a transgenic rat model of Huntington disease - Faure, Alexis; Es-seddiqi, Mouna; Brown, Bruce L.; Nguyen, Hoa P.; Riess, Olaf; Von Horsten, Stephan; Le Blanc, Pascale; Desvignes, Nathalie; Bozon, Bruno; El Massioui, Nicole; Doyère, Valérie (Frontiers in Behavioral Neuroscience, 2013)
Huntington’s disease (HD) is characterized by triad of motor, cognitive and emotional symptoms along with neuropathology in fronto-striatal circuit and limbic system including amygdala. Emotional alterations, which have a negative impact on patient well-being, represent some of the earliest symptoms of HD and might be related to the onset of the neurodegenerative process. In the transgenic rat model (tgHD rats), evidence suggest emotional alterations at the symptomatic stage along with neuropathology of the central nucleus of amygdala (CE). Studies in humans and animals demonstrate that emotion can modulate time perception. The impact of emotion on time perception has never been tested in HD, nor is it known if that impact could be part of the presymptomatic emotional phenotype of the pathology. The aim of this paper was to characterize the effect of emotion on temporal discrimination in presymptomatic tgHD animals. In the first experiment, we characterized the acute effect of an emotion (fear) conditioned stimulus on temporal discrimination using a bisection procedure, and tested its dependency upon an intact central amygdala. The second experiment was aimed at comparing presymptomatic homozygous transgenic animals at 7-months of age and their wild-type littermates (WT) in their performance on the modulation of temporal discrimination by emotion. Our principal findings show that (1) a fear cue produces a short-lived decrease of temporal precision after its termination, and (2) animals with medial CE lesion and presymptomatic tgHD animals demonstrate an alteration of this emotion-evoked temporal distortion. The results contribute to our knowledge about the presymptomatic phenotype of this HD rat model, showing susceptibility to emotion that may be related to dysfunction of the central nucleus of amygdala.